Tuning of tetrathiafulvalene properties: versatile synthesis of N-arylated monopyrrolotetrathiafulvalenes via Ullmann-type coupling reactions - Azov, Vladimir A.; Janott, Diana; Schlüter, Dirk; Zeller, Matthias (Beilstein Journal of Organic Chemistry, 2015)
An Ullmann-type coupling reaction was employed for the preparation of several N-arylated monopyrrolotetrathiafulvalenes with variable substitution patterns. Spectroscopic and electrochemical properties of the coupling products strongly depend on the electronic nature of the aromatic substituents due to their direct conjugation with the tetrathiafulvalene chromophore. The crystal packing of the arylated monopyrrolotetrathiafulvalenes is primarily defined by networks of C–H···X weak hydrogen bonds and short S···S contacts involving the tetrathiafulvalene moieties.
Keywords: cyclic voltammetry; N-arylation; pyrrolotetrathiafulvalene; Ullmann-type coupling; X-ray crystallography